Rapid evidence review of harm reduction interventions and messaging for people who inject drugs during pandemic events: implications for the ongoing COVID-19 response - Rebecca Wilkinson (Harm Reduction Journal, 2020)
Abstract Background People who inject drugs are at increased health risk in a pandemic due to their greater susceptibility to severe disease and as a consequence of the restrictions put in place to halt the spread of infection. Harm reduction (HR) services, which aim to reduce the negative effects of drug use on health, are likely to be diminished in a pandemic. However, innovative HR interventions and messaging may also develop in response to such a crisis. It is vital to understand the most effective ways to deliver HR in pandemic situations so that guidance can be provided for current and future disruptions to service provision. Methods A rapid evidence review was conducted with the aim of exploring what HR interventions and messaging are most effective during a pandemic-type situation. Ten health databases were systematically searched using terms relevant to the research aim. A search was also made of grey literature, including a targeted search of HR messaging from key national and service provider websites. Results In the initial search, 121 pieces of evidence were identified which, after screening and de-duplication, resulted in 60 for inclusion. The included evidence consists mainly of non-peer reviewed, pre-publication or expert opinion pieces. The rapid findings suggest that HR services should be deemed essential during a pandemic, with staff supported to work safely and social distancing adaptations implemented. Services should be encouraged to operate more flexibly; for instance, in deciding the amounts of take-home supplies of injecting equipment and medications. The evidence on HR communication was very limited but key messages on infection control, uncertain drug supply and accessing services were identified. Conclusions This rapid evidence review identifies implications for national policy makers, commissioners and HR service providers. A person-centred rather than disease-centred approach to HR delivered by collaborating partners, as well as prioritizing tailored HR messaging, is recommended. Further research evaluating the delivery of HR services and messaging, particularly focusing on health inequalities, is urgently needed.